Strategi Pedagang Pasar Tradisional dalam Menentukan Harga Jual Ikan Kakap Putih - Ferdinand Situmorang; Ade Sri Ulita (EKONOMI & SOSIAL, 2021)
As one of the livelihoods, barramundi traders in Merauke City determine the profitable selling price determination strategy influenced by profit, product and cost factors. The purpose of this study is to find out the strategy of determining the selling price of fish that benefits traders as well as the factors that affect it. This study is a field survey study with the population as a saturated sample. Research data is collected in the form of interviews, and questionnaires. This research method is qualitative and quantitative method. The results showed traders used 6 strategies from 7 strategies in determining the selling price of profitable fish, namely distribution strategies, promotional strategies, quality strategies, psychological pricing strategies, competitive pricing strategies, discounts and cost-based pricing, while in partial tests showed costs affect selling price determination and simultaneously profit, product and cost affect the selling price of barramundi.